Decreased secondary faecal bile acids in children with ulcerative colitis and Clostridioides difficile infection. Issue 6 (4th July 2021) - Rotondo‐Trivette, Sarah; Wang, Beibei; Gayer, Christopher; Parsana, Riddhi; Luan, Yihui; Sun, Fengzhu; Michail, Sonia
Summary: Background: Patients with ulcerative colitis (UC) have an increased risk of Clostridioides difficile infection (CDI). There is a well‐documented relationship between bile acids and CDI. Aims: To evaluate faecal bile acid profiles and gut microbial changes associated with CDI in children with UC. Methods: This study was conducted at Children's Hospital Los Angeles. Faecal bile acids and gut microbial genes related to bile acid metabolism were measured in 29 healthy children, 23 children with mild to moderate UC without prior CDI (UC group), 16 children with mild to moderate UC with prior CDI (UC+CDI group) and 10 children without UC with prior CDI (CDI group). Results: Secondary faecal bile acids, especially lithocholic acid (3.296 vs 10.793, P  ≤ 0.001) and ursodeoxycholic acid (7.414 vs 10.617, P  ≤ 0.0001), were significantly lower in children with UC+CDI when compared to UC alone. Secondary faecal bile acids can predict disease status between these groups with 84.6% accuracy. Additionally, gut microbial genes coding for bile salt hydrolase, 7α‐hydroxysteroid dehydrogenase and 7α/β‐dehydroxylation were all diminished in children with UC+CDI compared to children with UC alone. Conclusions: Bile acids can distinguish between children with UC based on their prior CDI status. Bile acid profile changes can be explained by gut microbial genes encoding for bile salt hydrolase, 7α‐hydroxysteroid dehydrogenase and 7α/β‐dehydroxylation. Bile acid profiles may be helpful as biomarkers to identify UC children who have had CDI and may serve as future therapeutic targets. Abstract : Fecal lithocholic acid and ursodeoxycholic acid are reduced in children with UC who have a history of CDI compared to children with UC without CDI. This is likely a result of decreased bacterial genes related to bile acid metabolism, including BSH, 7 alpha HSDH, and select bai genes.